ERBAN post-diplôme : 1997-1998. - Raynaud, Patrick; Carrayrou, Stéphane; Lepeut, Philippe; Ecole Régionale des Beaux-Arts de Nantes, Nantes (Nantes : ERBAN - Ecole Régionale des Beaux-Arts de Nantes, 1998)
Delprat, Nicolas ; Derrider, Micha ; de Sterk, Anne ; Garrido, Laetitia ; Jacq, Philippe ; Palomar, Sandra ; Roncin, Aurélie ; Touratier, Maxime ; Provoost, Ivo ; Denicolai, Simona
post-diplôme, Ecole Régionale des Beaux-Arts de Nantes, Nantes, du 26 mai au 30 juin 1998.
kunstcatalogus